Loss-consumed model of local computer network protection - Лащевский, В. И.; Зеленков, Д. А. (Proceedings of National Aviation University (archive), 1999)
Considered is a loss-consumed model of local computer network protection. The model allows to conceptually determine the protection strategy and optimal, from economic point of view, means of protection. Proposed is a practical method of determining the risk rate of safe local network